Involvement of key stakeholders in controlling animal diseases in rural settings: Experiences with African swine fever in Uganda - Peter Ogweng, Charles Masembe , Johnson Francis Mayega , Ibrahim Keeya , Charles Tumuhe , Rodney Okwasiimire and Vincent Muwanika (African Journal of Pig Farming, 2019)
Key stakeholders’ involvement in the design and enforcement of effective African swine fever (ASF) biosecurity measures is very vital. Unfortunately, many times key stakeholders are less involved in the policy designing process. This study analyzed information from stakeholders in Mukono District, to assess the acceptability of enforcing ASF biosecurity measures among key stakeholders. Mukono District has a high density of pigs and a history of frequent ASF outbreaks. Key informants (n = 23) were identified and interviewed in four sub-counties to generate an ASF control stakeholders’ list. Eleven stakeholder groups were identified by the Key Informants. Sixty participants representing different stakeholder groups identified through the Key Informant interviews participated in a workshop to assess stakeholders’ characteristics regarding strict enforcement of ASF control measures. Stakeholder grid analysis revealed 60% as drivers, and 40% as supporters. There were no blockers, abstainers, and bystanders. Despite this, majority of the groups (90%) did not have adequate capacity to implement the intervention due to financial constraints and inadequate technical support. These results show that there is great support for enforcement of biosecurity measures if stakeholders are facilitated with financial and technical support thereby limiting outbreaks of ASF in rural areas of Uganda.